IMPROVING THE IMPLEMENTATION OF THE PRIDE CULTURE AT UNIVERSITAS BINA DARMA USING PERSUASIVE TECHNOLOGY - Amin, Zaid; Helmi, Sulaiman; Kusumadya, M. Agil (STKIP PGRI Tulungagung, 2024)
The concept of quality culture in higher education must go beyond surface-level slogans; it requires genuine alignment between internal stakeholders and institutional values. When this alignment weakens, employee commitment and organizational loyalty may decline, threatening long-term competitiveness. At Universitas Bina Darma (UBD), fostering a strong quality culture is essential. This study investigates the implementation of the PRIDE (Persistent, Responsive, Innovative, Disciplined, Excellent) quality culture at UBD and proposes strategies to enhance it through gamification. Using a mixed-methods approach, the research combines qualitative data from interviews and observations with quantitative analysis via Structural Equation Modeling (SEM). Gamification experiments are designed to promote engagement and adoption of PRIDE values, integrating persuasive technology and internal marketing theory. The study maps current practices, tests gamified interventions, and evaluates their impact on continuous improvement. Findings offer a measurable understanding of PRIDE culture execution and practical strategies for strengthening quality culture in higher education.